The Mediterranean and Eastern Atlantic species of Spinolambrus Tan & Ng, 2007: S. macrochelos (Herbst, 1790), S. notialis (Manning & Holthuis, 1981), and S. verrucosus (Studer, 1883), with a note on the identity of Lambrus spinosissimus Osório, 1923 (Crustacea: Decapoda: Brachyura: Parthenopidae) - Tan, S. H.; Low, Martyn E.y. (Zootaxa, 2014)
Spinolambrus Tan & Ng, 2007, was established for eight species of parthenopid crabs, with members of the genus characterised by the presence of two spine-like teeth on the upper margin of the third maxilliped merus, and one tooth on the upper margin of the propodus (Tan & Ng 2007: 111). Three species of Spinolambrus, are found in the Mediterranean and Eastern Atlantic regions: Cancer macrochelos Herbst, 1790 (type species by original designation), Parthenope notialis Manning & Holthuis, 1981, and Lambrus verrucosus Studer, 1883.